Degradation of palm oil mill secondary effluent (POMSE) using biostructure - Abd. Wahid, Nurul Bahiyah (2007)
Biostructure treatment is one of the latest biotechnology applications in environmental engineering. In this study, the biostructure treatment was used to treat the palm oil mill secondary effluent (POMSE). Biostructure is comprised of cement, aggregates, sand, zeolite, lightweight aggregates, granular activated carbon (GAC), water and microorganisms. In this study, biofilm was developed to increase the biostructure’s performance. Seven types of microbes were used consist of microbe A, B, C, S1, S2, ADL1 and ADL2, which were isolated from textile wastewater, Sg Segget and fermented food. The microorganisms grew on the surface of the biostructure in the form of biofilm and degrade the waste, hence treating the POMSE. The three reactors that were used to treat POMSE in this study comprised of reactor A (10 biostructures), reactor B (5 biostructures) and reactor C (without biostructure) that acted as a control. Results obtained showed that 10 biostructures in the 5-liter batch reactor gave the average removal of colour of 51%, COD of 42%, TOC of 42% and SS of 80% in 4 days HRT, whereas 5 biostructures able to remove 48% colour, 37% COD, 35% TOC and 70% SS. The results showed that the efficiencies of the biostructure treatment depend on the surface area of biostructures and the retention time. More biostructures resulted in higher degradation of POMSE. From the survivability test, only three out of seven microbes developed at the early stage of biofilm development survived at the end of the experiments, namely microbe A, B and ADL1. It can be concluded that biostructure treatment is a viable polishing treatment of POMSE before being discharged into the river.